DETERMINATION OF BETALACTAMIC ANTIBIOTIC RESIDUES USING AN IMMUNOENZYMATIC ASSAY IN MILK OF COWS TREATED AGAINST MASTITIS - Salas Z., Paúl (2013)
The aim of the study was to determine the frequency of antibiotic residues in milk from cows that had clinical mastitis and returned to production after completion of the 3- day period of discarded milk post treatment. Milk samples were collected from 60 cows that received treatment for mastitis with betalactamic antibiotics. Samples were analyzed by the inmunoenzimatic test SNAP (Betalactam), which indicates presence of betalactamic antibiotics residues in milk. Results showed that 45.0% (27/60) were positive to betalactamic antibiotics residues. Also, 56.0% (14/25), 26.7% (4/15), and 45% (9/20) of samples from animals treated with penicillin and streptomycin, kanamycin and penicillin, and amoxicillin and clavulanic acid respectively had antibiotic residues. In addition, 50.0% (14/28) of the animals treated by the intramuscular route and 40.6% (13/32) by the intramammary route were positive; whereas 46.7% (7/15), 57.1% (12/21), and 33.3% (8/24) of cows with low, medium, and high production cows, respectively, were positive to the test. However, no statistical association between type of antibiotic used, via of administration and level of production with presence of antibiotic residues was found.